Optimization of a multi-generation power, desalination, refrigeration and heating system - Pietrasanta, Ariana M.; Mussati, Sergio F.; Aguirre, Pio A.; Morosuk, Tatiana; Mussati, Miguel C. (Energy (Oxford), 2022)
The optimization of a multi-generation system which represents the integrated dual-purpose desalination plant and a low-scale absorption refrigeration system is addressed. A nonlinear mathematical programming optimization model that integrates a natural gas combined-cycle, a multi-effect distillation desalination plant, a series flow double-effect water-lithium bromide absorption refrigeration system, and a water heater, is developed based on first-principle models. The model is implemented in General Algebraic Modelling System and a generalized gradient-based optimization algorithm is used. Given design specifications for electricity generation (around 37 MW), freshwater production (100 kg/s), refrigeration capacity (2 MW), and thermal load for heating (around 0.7 MW of hot water), the integrated system is optimized by minimizing two objective functions by single-objective optimization: total heat transfer area and total annual cost. As a result, minimum total heat transfer area values of 39148 m2, 36002 m2, and 35161 m2 are obtained when 4, 5, and 6 distillation effects were considered in the multi-effect distillation system, respectively. Also, a minimum annual cost of around 24 MM$/yr. is obtained for 5 distillation effects. The influence of the number of effects in the multi-effect distillation subsystem on the optimal solutions is analyzed. Cost-effective optimal solutions are developed for the studied multi-generation system. •A multi-generation system is integrated for power, freshwater, cooling, and heating.•NLP model for simultaneous optimization is proposed and gradient-based method is used.•The total heat transfer area (THTA) of the entire process is minimized.•The total annual cost (TAC) of the entire process is minimized.•A minimum TAC of 23.9 MM$/yr. is found when five-effect MED desalination unit is used.